An Overview of Corruption and its Challenges to Nigeria’s National Development - Zango, Abdul-Aziz Sani; Mohammed, Isah Shehu (Kashere Journal of Politics and International Relations, 2025)
Corruption is a prevalent challenge to most organisations and countries of the world. Although its practice and prevalence are relative, it has been one major inhibiting factor for any state, societal development and humankind generally. Nigeria has been one of those worst hit it impeding and her national development since her independence with many and multi-faceted effects against national development. This study makes an overview of corruption, its practice, prevalence, causes and the stakeholders in Nigeria. The study is qualitative and uses secondary sources of data. The theory of prebendalism is used to build the theoretical basis. The paper focuses on public corruption and highlights the major causes, the stakeholders, the high-profile corruption cases, as well as identification of the major culprits of corruption in Nigeria, especially in the public sector and the major national development plan, programmes and projects which all suffer as a result of corruption. The paper advances the argument that Nigeria has economic potentialities capable of achieving the highest level of national development. However, incessant corruption that cut across all sectors of the state has been inhibiting achieving national development. Some key recommendations, including stiff penalties, synergy among anti-corruption agencies, extensive and intensive education and enlightenment, and genuine political will and commitment to fight corruption in order to achieve meaningful and sustainable national development in a least corrupt Nigerian state.